Spatial-Science-based approach in Planning Framework for Multimodal Public Transport: Case Study of Melaka, Malaysia - Kamal Baharin, S. S. (2011)
The massive growth of movement due to urbanization process increases the challenge to manage a transportation system efficiently. An efficient management of transportation is vital for Melaka as a tourism state of Malaysia. The growth of tourism industry is thriving by the increasing number of travelers. Melaka has different types of travelling modes to cater different trip purposes and traveler groups. A mixed traffic imposes certain types of difficulties for users as well as planners. The different modes (multimodal) of travelling (i.e. public or private transport) provide options for a traveler to plan the journey. Unfortunately, different transport modes without synchronization strategies caused difficulties in planning a trip in advance. This paper focuses on multi-modal planning of public transport. A mixed traffic imposes certain types of difficulties for users as well as planners. In reality, the public transport use pre-planned and experienced-based route approach in transport planning process. This paper investigates and proposes the use of spatial technology into the planning framework of multimodal public transport system for planning and decision-making purposes. As a result, the planning framework acts as a tool to improve planning and management in public transport. The use of spatial technology under different phases of the framework enables to see the spatial heterogeneity of the elements and the processes involved. In addition it promotes synchronize, strategic and collaborative approach to planning.